The effect of instructions on verbal correspondence in individuals with autism (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Two children and one adolescent diagnosed with autism participated in the study. The effects of general and specific rules on verbal correspondence between doing and saying was investigated using Matching to Sample (MTS) tasks. After each MTS trial, participants had to report if they performed the task correctly or not. The consequences for correct reports were manipulated in three experimental conditions: baseline, reinforcement for reports of correct responding, reinforcement for reports with correspondence and return to the baseline. The reinforcement for reports of correct responding condition was divided into: no instruction, with general instruction (description of the behavior-consequence relationship), and specific instruction (description of the antecedent-behavior-consequence relationship). Distortions were much more numerous in the error reports and did not vary according to the experimental conditions. Variability among participants’ responding was observed, but overall the results replicated the literature findings with typically developing participants.
Keywords: verbal correspondence, autism, performance self-report, rules